Strategy for Developing the Ecotourism Attraction of Baturiti Waterfall in the Parigi Moutong Area, Central Sulawesi - Ni Putu Nurhayati; I Ketut Darma (Universitas Warmadewa, 2023)
Baturiti Waterfall in the Parigi Moutong tourist area, Central Sulawesi offers tourism packaging that prioritizes pristine and natural potential so that it becomes the center of attention of tourists to visit, besides that support from tourism stakeholders for the development of Baturiti Waterfall Ecotourism Attraction is very important to develop the potential that exists in Baturiti Waterfall. This study aims to examine the development strategy of attraction of Baturiti waterfall ecotourism in Parigi Moutong, Central Sulawesi. Data analysis used is SWOT Analysis and Cartesian Diagram Analysis. Based on the results of the research, it shows that by involving local communities in Baturiti Waterfall Ecotourism activities, they can develop sustainable tourism. By developing a good promotion system, it will be able to minimize existing threats and be able to increase the number of tourist visits. Facilities at Baturiti Waterfall also still need to be developed for the convenience of visitors.